Using the One Health approach to prevent and manage zoonotic diseases - Bett, Bernard K. (Global Landscapes Forum, 2020)
Several years ago, a scientific assessment declared that the future costs of disease pandemics could be in the same order as those of climate change. As the ongoing novel coronavirus pandemic continues to upend lives and economies, those costs are becoming clearer by the day. Yet funding and policy leadership for stopping or managing pandemics receives only a fraction of that invested in managing a warming globe. A new research-based report published jointly by the United Nations Environment Programme (UNEP) and the International Livestock Research Institute (ILRI) provides an overview of how COVID-19 and other zoonotic diseases emerge and spread. Experts will describe a ‘One Health’ approach linking human, animal and environment health, with a focus on agriculture and biodiversity, that can prevent and mitigate future pandemics. The session will provide practical policy and investment options for adopting integrated One Health approaches.